2022
DOI: 10.3390/biomedicines10050998
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid in Classical Trigeminal Neuralgia: An Exploratory Study on Candidate Biomarkers

Abstract: Trigeminal neuralgia (TN) is a severe type of facial pain. A neurovascular conflict between cranial nerve V and a nearby vessel is the main pathophysiological mechanism, but additional factors are likely necessary to elicit TN. In this study, the primary aim was to explore differences in protein expression in the cerebrospinal fluid (CSF) of TN patients in relation to controls. Methods: Sixteen TN patients treated with microvascular decompression and 16 control patients undergoing spinal anesthesia for urologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
(44 reference statements)
1
8
0
Order By: Relevance
“…This TN subtype often has an earlier onset than TN with NVC (Hardaway et al, 2019; Ko et al, 2015), which would be in line with that the female patients showed an earlier increase in incidence in our study. In addition, females generally exhibit an increased propensity to develop various autoimmune diseases and inflammatory conditions (Quintero et al, 2012) and this may also involve the risk to develop TN since inflammatory pathophysiological mechanisms seem to be relevant both in primary (Ericson et al, 2019; Svedung Wettervik et al, 2022) and secondary TN (e.g. MS) (Cruccu et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This TN subtype often has an earlier onset than TN with NVC (Hardaway et al, 2019; Ko et al, 2015), which would be in line with that the female patients showed an earlier increase in incidence in our study. In addition, females generally exhibit an increased propensity to develop various autoimmune diseases and inflammatory conditions (Quintero et al, 2012) and this may also involve the risk to develop TN since inflammatory pathophysiological mechanisms seem to be relevant both in primary (Ericson et al, 2019; Svedung Wettervik et al, 2022) and secondary TN (e.g. MS) (Cruccu et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Trigeminal neuralgia (TN) is typically characterized by brief, paroxysmal episodes of intense facial pain, located in any of the cranial nerve V (CN V) branches (Bendtsen et al, 2020; Cruccu et al, 2020; ICHD, 2013). Classical TN is attributed to a neurovascular conflict (NVC) between a cerebral vessel and CN V in the root entry zone (ICHD, 2013; Thomas & Vilensky, 2014), although additional mechanisms such as ion‐channel disturbances and neuroinflammation with arachnoiditis may also be involved in disease progression (Abu Hamdeh et al, 2020; Bendtsen et al, 2020; Ericson et al, 2019; Gambeta et al, 2020; Mazzucchi et al, 2019; Svedung Wettervik et al, 2022; Thomas & Vilensky, 2014). In addition, secondary TN caused by, e.g., multiple sclerosis (MS) lesions of the CN V pathways as well as idiopathic TN when no specific cause can be found are other subtypes of TN with slightly different pathophysiology (Gambeta et al, 2020; ICHD, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…We intentionally chose to collect cisternal CSF from around the trigeminal nerve in patients undergoing MVD, based on the rationale that this might enhance the sensitivity of our TN CSF samples to the inflammatory environment experienced by trigeminal neurons compared with previous studies that solely used lumbar puncture CSF samples distant from the site of TN pathology. 1 , 18 , 46 Ethical challenges obviously prevented us from extracting cisternal CSF from completely healthy populations. Although it is true that cisternal CSF may be encountered in a variety of neurosurgical procedures, the vast majority of these are for tumor-related surgery, in which a confounding pro-inflammatory local environment is highly likely to be present; consequently, we limited cisternal control CSF collection to HFS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Collection of cisternal CSF from the region of the trigeminal nerve is a novel approach in comparison with previous studies of CSF in patients with TN, which have collected CSF solely via lumbar puncture. 1 , 18 , 46 For control patients with NPH and an implanted lumbar drain, CSF samples of 2.5 to 5 mL were collected using a sterile collection apparatus and transported on ice from the ward to the laboratory. All samples were immediately centrifuged at 1800 rpm for 5 minutes to remove any contaminant cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation